Does telerehabilitation result in inferior clinical outcomes compared with in-person care for the management of chronic musculoskeletal spinal conditions in the tertiary hospital setting? A non-randomised pilot clinical trial. (September 2021) - Cottrell, Michelle A; O'Leary, Shaun P; Raymer, Maree; Hill, Anne J; Comans, Tracy; Russell, Trevor G
Introduction: Clinical guidelines recommend multidisciplinary non-surgical management for most musculoskeletal spinal conditions. Access to such services continues to be a barrier for many individuals residing outside metropolitan regions. The primary aim of this study was to determine whether clinical outcomes achieved via telerehabilitation are as good as those achieved via in-person care. Methods: A non-randomised pilot clinical trial was undertaken where eligible patients chose to access treatment either via telerehabilitation or in-person (control group). Outcome measures for pain-related disability, pain severity and health-related quality of life were recorded at baseline, 3-, 6- and 9-months. Secondary outcomes included patient satisfaction and technical disruptions. Results: Seventy-one patients were recruited (telerehabilitation, n = 51; control group, n = 20). Patient characteristics did not differ at baseline and clinically meaningful improvements for pain-related disability and health-related quality of life were observed in both groups. Non-inferiority of telerehabilitation could not be claimed for any clinical outcome measure. There were no significant group-by-time interactions observed for either pain-related disability ( p = 0.706), pain severity ( p = 0.187) or health-related quality of life ( p = 0.425) measures. The telerehabilitation group reported significantly higher levels of treatment satisfaction (median: 97 vs. 76.5; p = 0.021); 7.9% of telerehabilitation appointments were not completed due to technical disruptions. Discussion: Findings indicate patients with chronic musculoskeletal spinal conditions can achieve clinically meaningful improvements in their condition when accessing care via telerehabilitation. Telerehabilitation should be considered for individuals unable to access relevant in-person services; however non-inferiority remains inconclusive and requires further exploration.